Knockdown of circ-FURIN suppresses the proliferation and induces apoptosis of granular cells in polycystic ovary syndrome via miR-195-5p/BCL2 axis - Yongqian Chen (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is an endocrine disease that increases the risk of infertility. Circular RNAs (circRNAs) play important roles in regulating the biological processes of PCOS. Our study was designed to explore the function of circ-FURIN in PCOS. Methods Circ-FURIN expression was detected using RT-qPCR. The protein expression of AVEN, BCL2, XIAP and AREL1 was measured using western blot. Dual-luciferase reporter and RNA pull-down assays were applied to clarify the interaction between miR-195-5p and circ-FURIN or BCL2. Functionally, cell proliferation was assessed by MTT and colony formation assays. Cell apoptosis was analyzed by flow cytometry. Results Circ-FURIN was upregulated in PCOS patients and granular cells (GCs). Knockdown of circ-FURIN inhibited cell proliferation and promoted apoptosis of KGN cells, along with the increased expression of caspase-3 and Bax and the decreased levels of p-PI3K. Gene ontology (GO) analysis indicated circ-FURIN is associated with apoptotic signaling pathway and cell death. Subsequently, BCL2 expression was elevated in patients with PCOS and positively regulated by circ-FURIN. Furthermore, circ-FURIN was served as a sponge of miR-195-5p to directly target to BCL2. The levels of miR-195-5p were reduced in PCOS and KGN cells. Knockdown of circ-FURIN decreased the expression of BCL2, which was abolished by miR-195-5p inhibitor. At last, rescue experiments revealed that overexpression of BCL2 reversed the effects of circ-FURIN knockdown on cell proliferation and apoptosis of KGN cells. Conclusions Loss of circ-FURIN alleviated the development of PCOS via miR-195-5p/BCL2 axis. Circ-FURIN may be the novel biomarker for PCOS.